Warriors and Weavers: The Poetics and Politics of Indigenous Appropriations of New Media Technologies in Latin America. Issue 1 (12th July 2018) - Pitman, Thea
There has been much academic debate about the relationship of indigenous communities to new media technologies, specifically with respect to the way that the former might appropriate the latter and the terms in which they might do so, with a significant number of critics arguing that the concepts and lexicon of the traditional practice of weaving, sometimes recast as 'netweaving', may offer the most appropriate trope. However, such arguments typically remain at the level of theory, providing little or no evidence of the way in which real indigenous communities speak of how they appropriate new technologies. This article explores the poetics and underlying politics of indigenous appropriations of new media technologies, with reference to aesthetics where relevant, by contrasting the online presence of two highly prominent, prize-winning projects of indigenous internet appropriation: the web portal Índios Online, run by a group of different indigenous communities in north-eastern Brazil, and the homonymous website of the Asociación de Cabildos Indígenas del Norte del Cauca of the Nasa community in south-western Colombia. While they have both been studied extensively in their national contexts, very little attention has been paid to the poetics and aesthetics of the different projects, and no previous study has taken a sustained comparative approach. I present evidence to demonstrate that while the latter do, to some extent, engage tropes of weaving in their appropriation of these technologies, the former tend to prefer hunter and/or warrior tropes. I argue that the greater or lesser involvement of indigenous women in the appropriation of new media technologies does not seem to be a major factor determining such a choice, despite the typically gynocentric practice of weaving and hence the feminisation of related discourse, and, in contrast, the more masculinist repertoire of hunter and warrior tropes. Instead, I find that the different geographical locations, traditional activities, artisanal production and, most importantly, the immediate political situation and processes of the different communities do impact significantly on this choice.